Analysis Corporate Social Responsibility (CSR) in the Implementation of the Scholarship Program by PT. Siam Cement Group (SCG) Indonesia in DKI Jakarta Province whose Schools have a Partnership with SCG - Abdulroman Ngopulae (Budapest International Research and Critics University, 2022)
The purpose of this study aims to explain the implementation of the scholarship program and the benefits of scholarships in the concept of social welfare related to human capital development (HCD), social assistance, social investment, corporate social responsibility (CSR), and scholarships. Based on previous studies, these four concepts have not been studied in an integrated manner. Social welfare has not been specifically linked to HCD; HCD has not been linked to the scholarship program, and scholarship programs have not been specifically linked to a company's CSR. That is why social welfare in this study is associated with HCD. HCD is one of the three important capital causes of economic growth and in turn can improve social welfare. One of the important implementations of HCD is education. Efforts to increase the opportunity to obtain an education, among others, through scholarship programs. Scholarships can be held by the government or the private sector. Private companies run scholarship programs usually in the name of CSR programs. Starting from this thought, this study aims to examine how a private company provides scholarships in the context of CSR, and the extent to which the scholarship program has concrete positive implications for HCD.